2022
DOI: 10.4103/jfmpc.jfmpc_580_21
|View full text |Cite
|
Sign up to set email alerts
|

A review of the neurological complications of breast cancer

Abstract: Conducting broad assessments of the main burden of breast cancer is the core factor for improving overdiagnosis and overtreatment of breast cancer patients as well as their survival rates. Breast cancer patients may experience neurological complications that cause devastating effects on them. Chemotherapy-induced peripheral neuropathy (CIPN) and neuropathic pain are two of the most reported complications. Objective: This study aims to review the neurological complications of breast cancer and the ways to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Many of these syndromes are mediated by antibodies targeting specific antigens of neurons [ 11 ]. Of note, immunosuppressive treatments can also impact the central nervous system by increasing susceptibility to opportunistic infections [ 12 ]. In the case discussed in this paper, the patient has a prior history of metastatic breast cancer and has developed secondary symptoms of DPPX antibody-mediated encephalitis and retinopathy following immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these syndromes are mediated by antibodies targeting specific antigens of neurons [ 11 ]. Of note, immunosuppressive treatments can also impact the central nervous system by increasing susceptibility to opportunistic infections [ 12 ]. In the case discussed in this paper, the patient has a prior history of metastatic breast cancer and has developed secondary symptoms of DPPX antibody-mediated encephalitis and retinopathy following immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of therapeutic advancements, the microbiota may play a crucial role in predicting individual breast cancer risk and prognosis, as well as the pharmacokinetics, pharmacodynamics, and clinical efficacy of treatments 41,131 . Recent research has revealed that certain gut commensals, which are present in excess in breast cancer patients compared to healthy individuals, have a negative impact on breast cancer prognosis, are influenced by chemotherapy, and may also affect weight gain and neurological side effects of breast cancer therapies 132,133 . Clinical researchers are therefore interested in the potential of the gut microbiota as a biomarker for predicting the efficacy of cancer treatment.…”
Section: Technological Advances In Breast/gut Microbiome Research: a ...mentioning
confidence: 99%
“… 41 , 131 Recent research has revealed that certain gut commensals, which are present in excess in breast cancer patients compared to healthy individuals, have a negative impact on breast cancer prognosis, are influenced by chemotherapy, and may also affect weight gain and neurological side effects of breast cancer therapies. 132 , 133 Clinical researchers are therefore interested in the potential of the gut microbiota as a biomarker for predicting the efficacy of cancer treatment. Studies have shown that the gut microbiota can modulate cancer treatments' efficacy and adverse effects, and that cancer and anticancer therapies interact bidirectionally with the gut microbiota.…”
Section: Technological Advances In Breast/gut Microbiome Research: a ...mentioning
confidence: 99%
“…While breast cancer primarily affects the breast tissue, it can have far-reaching consequences throughout the body, including the brain. The development of neurological complications in breast cancer patients can significantly impact their quality of life, treatment options, and prognosis [ 2 ]. Neurological complications encompass a wide range of conditions, from brain metastases to paraneoplastic syndromes and cognitive impairments resulting from cancer treatments [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The development of neurological complications in breast cancer patients can significantly impact their quality of life, treatment options, and prognosis [ 2 ]. Neurological complications encompass a wide range of conditions, from brain metastases to paraneoplastic syndromes and cognitive impairments resulting from cancer treatments [ 2 ]. Patients experiencing neurological complications may suffer from symptoms such as headaches, seizures, cognitive deficits, motor impairments, and psychological distress.…”
Section: Introductionmentioning
confidence: 99%